PUBLIC-PRIVATE PARTNERSHIP AS A DRIVER OF POST-WAR RENOVATION OF TOURIST INFRASTRUCTURE IN UKRAINE - KARPENKO, Yurii (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article is devoted to substantiating the theoretical and methodological foundations and developing recommendations for the implementation of public-private partnership mechanisms as a key institutional and organisational mechanism for the post-war restoration of tourism infrastructure. Public-private partnerships are a key institutional and organisational mechanism for the post-war reconstruction of tourism infrastructure, as they ensure the attraction of critically needed private capital (including foreign investment), effective management competencies and enables the implementation of state socio-economic development tasks based on long-term cooperation and shared responsibility. The synergy effects of public-private partnership ensure the coordination of actions between the public and private sectors around the interests of consumers, which stimulates the development of the tourism industry by implementing an anti-entropy strategy through the inflow of investment and innovation. The implementation of public-private partnership projects in war-affected regions is burdened by a unique range of security, legal, financial and political risks. The choice of public-private partnership model depends on the areas in which the agreement is implemented. Models of public-private partnerships and mechanisms for their adaptation for post-war restoration of tourism infrastructure are disclosed. It is confirmed that the success of public-private partnership in the post-war restoration of Ukraine’s tourism infrastructure critically depends on the state’s ability to effectively assume or minimise risks that are atypical for commercial projects, which can be achieved through the introduction and use of relevant risk distribution and minimisation mechanisms (creation of a National Military Risk Insurance Fund; comprehensive insurance and risk distribution in contracts; administrative optimisation and implementation of a «Fast-Track» procedure for key stages of project implementation; use of escrow accounts to finance projects). Together, these mechanisms provide the necessary regulatory and financial guarantees, which are a prerequisite for attracting long-term investment in the reconstruction of tourism infrastructure.